Belief propagation-based joint iterative algorithm for detection and decoding in asynchronous CDMA satellite systems - Gu, Na; Wu, Sheng; Kuang, Linling; Ni, Zuyao; Lu, Jianhua (EURASIP journal on wireless communications and networking, 2013)
As the geostationary orbit (GEO) is congested in the commercial Ku band, the adjacent satellites will receive the interference from small aperture terminals which have a wide field of view. To reduce the interference toward the adjacent satellites, code division multiple access (CDMA) with spread spectrum needs to be adopted in the satellite communications on-the-move system. However, the mutual interference between CDMA users leads to the performance loss, which is not acceptable for the power-sensitive small aperture terminals, and the computation complexity is still an intractable problem when the conventional iterative minimum mean square error (MMSE) scheme is employed to suppress the multiple access interference (MAI) in satellite systems especially that is coded by low-density parity-check (LDPC) code. Moreover, the long transmission delays of different users caused by the long transmission distance require the robustness of the interference suppression for the asynchronous case. In this paper, a joint chip-level algorithm for CDMA multiuser detection and LDPC decoding with a new and simple iterative structure based on belief propagation (BP) for satellite systems is developed, which integrates the iterations of multiuser detection and the iterations of LDPC decoding with factor graphs. Through analysis and simulations, it is verified that the proposed algorithm is robust to the asynchronous CDMA satellite system, and with the similar iterative complexity, the performance of the proposed algorithm outperforms that of the conventional iterative MMSE scheme in the asynchronous CDMA satellite system.